Temu Manten as Power Relation and Cultural Negotiation of Wedding Organizer: Surabaya Public Perspective - Afriansyah, Teddy; Riyanto, Edi Dwi; Afdholy, Nadya (Universitas Tanjungpura, 2025)
Wedding organizer who has been arranged in the role of organizing a meet and greet event are very important. It showed up from a cultural power and cultural negotiations that are owned between wedding organizer and the couple's family. So, the objectives of this research are 1) Explaining the form of power that can be exercised by the wedding organizer in the success of temu manten event and 2) Explaining the form of negotiation with cultural context that can be done by the Surabaya public to the wedding organizer. The method used in this research is descriptive qualitative. The results of the study found that 1) there is a form of power relations of the wedding organizer for temu manten event; a) Holding events/exhibitions for promotional events, b) Coordinating between the wedding organizer and the couple's family in depth, c) Preparing human resources from the wedding organizer by forming a committee, d) The wedding organizer must have flexibility and be able to adapt to the couple's family, and e) As an intercultural link from families with different cultural backgrounds. In addition, 2) there is a form of cultural context negotiation by the wedding organizer for temu manten event; a) Negotiating with a specific cultural approach, b) Conducting communication in rotation, c) Conducting negotiations based on consensus, and d) Giving appreciation to experts/professionals from the wedding organizer. So, the presence of forms of power and negotiations that arise, temu manten event is able to run as expected.